Influence on Internal Control Through Digitalization of Assets: A Study on Ministry of Interior, UAE - Ahmed Khamis, Ali Saeed Alkaabi; Joseph, Adaikalam; Asif, Mahbub Karim; Hock, Oo Yu; Mohammad Imtiaz, Hossain (2020)
Fixed assets management through digitalization has been always been a matter of concern for public organization, especially organization as strategic and important like Ministry of Interior, in the United Arab Emirates. Since there are huge assets procurement, its management and control keeping has been a daunting task always. The purpose of this research is to evaluate the influence of internal control through assets management’s digitalization. To carry on with the research work a survey questionnaire was designed. A structured questionnaire was used to collect data and SPSS was used to analyse them. From the finding of the survey it was observed that the pace of digitalization was not so fast moreover the control on the assets tracking system at times was difficult as the ministry deals with very sophisticated tangible equipment’s. Well, after examining the evaluation of fixed assets management through digitalization, a study on ministry of interior in UAE – the first objective of the study, it is seen that yet the application of the assets management through digitalization is not in that level so the performance is very poor. This study may inform managers of the importance of understanding the technology are a fundamental part of the business that requires its strategy. It may also have implications for the organization’s mentality towards internal factors concerning the technical systems.